Perancangan Sistem Informasi Buku Tamu Pada Fakultas Ilmu Komputer Di Universitas Bina Bangsa - Eryka Gading Sahara Colondam; Gagah Dwiki Putra Aryono; Maman Masyhuri (JURNAL MANAJEMEN PENDIDIKAN, 2025)
DESIGN OF A WEB-BASED GUEST BOOK INFORMATION SYSTEM AT THE FACULTY OF COMPUTER SCIENCE, BINA BANGSA UNIVERSITY USING THE LARAVEL FRAMEWORK Abstract. The advancement of information technology encourages higher education institutions to optimize administrative services digitally, including guest registration and academic document requests at the faculty level. This study aims to design a web-based guest book information system that supports two main features: lecturer appointment requests and academic document submissions. The system was developed using the Waterfall method, which includes analysis, design, implementation, and testing phases. Built with the Laravel framework, the system also integrates WhatsApp-based notifications. Test results indicate that the system performs well and is positively received by users. The system effectively improves administrative service efficiency, reduces queues, and ensures structured documentation. In conclusion, the implementation of this system contributes significantly to enhancing the quality of academic services at the faculty level.